Homology modelling and structural analysis of Phytases - Noorbatcha, Ibrahim Ali; Mohd. Salleh, Hamzah; Amid, Azura (2010)
Homology modeling is a powerful tool in predicting the three dimensional (3D) structure of a protein using a solved structure within the same family as template. Compared to other methods such as X-ray crystallography and NMR, homology modelling has the advantage of being a fast yet reliable technique in solving proteins’ 3D structures, starting from their amino acid sequences. In this study, homology modelling was used to obtain the 3D structure of two different phytases using only their amino acid sequence; phyFAUIA1_H which belongs to the histidine acid phosphatases, and Bacillus subtilis SAUIA243 which belongs to the β-propeller phytases. E. coli phytase (PDB code 1dkm) was used as a template for phyFAUIA1_H model with 99.512% sequence identity. On the other hand, Bacillus amyloliquefaciens (PDB code 2poo) was used as a template for B. subtilis SAUIA243 model with 71.268% sequence identity. The BLAST (Basic Local Alignment Search Tool) algorithm was used to find the highest scoring ungapped local alignment between the query and database sequences. This particular score uses the BLOSUM substitution matrix, which is a block substitution matrix that uses segments of blocks corresponding to the most highly conserved regions of proteins. Both models were evaluated and found to be quite satisfactory without being manually modified. Phytases are important constituents in Animal feed industry. These models can now be used to design new phytases, with improve properties such as enhanced enzyme activity, pH tolerance, and thermostability.